2014
DOI: 10.1155/2014/467105
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Toxicity Study in Rats of Two New Ethyl-Carbamates with Ixodicidal Activity

Abstract: Female and male Wistar rats were used to determine the subchronic oral toxicities of two new ethyl-carbamates with ixodicidal activities (ethyl-4-bromphenyl-carbamate and ethyl-4-chlorphenyl-carbamate). The evaluated carbamates were administered in the drinking water (12.5, 25 and 50 mg/kg/day) for 90 days. Exposure to the evaluated carbamates did not cause mortality or clinical signs and did not affect food consumption or weight gain. However, exposure to these carbamates produced alterations in water consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
5
0
3
Order By: Relevance
“…BW was measured weekly over the 12 weeks of the experiment; weight increases were detected. Normally, a rat will gain weight as it gets older, such as over the 3 months of the experiment [13]. Table 2 shows that the weight of the male rats increased by 6.28-9.19 g/week and that of the female rats increased by 7.59-9.03 g/week.…”
Section: Discussionmentioning
confidence: 99%
“…BW was measured weekly over the 12 weeks of the experiment; weight increases were detected. Normally, a rat will gain weight as it gets older, such as over the 3 months of the experiment [13]. Table 2 shows that the weight of the male rats increased by 6.28-9.19 g/week and that of the female rats increased by 7.59-9.03 g/week.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we observed that the ethyl-carbamates used in this study induce an increase in micronucleated reticulocytes in rats, which could be the result of DNA damage [ 10 ]. Furthermore, we observed an increase in thiobarbituric acid reactive species (oxidative stress) that can cause damage to macromolecules including DNA [ 8 ]. However, the results of the present study suggest that these ethyl-carbamates did not represent a risk for cancer in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of LQM 919 and LQM 996 must be evaluated before these compounds are proposed for the safe control of ticks. Following the criteria of the OECD, these carbamates are found to have low acute and subchronic toxicity in rats [ 8 , 9 ]. Nevertheless, these compounds produce an increase in micronucleated reticulocytes in the peripheral blood of rats as well as alterations in the cell cycle of human lymphocytes suggesting that these compounds cause DNA damage [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini juga telah diungkapkan oleh (Prado-Ochoa et al, 2014), berdasarkan survey menunjukkan adanya efek samping dari penggunaan obat tradisional. Toksisitas obat merupakan faktor terpenting yang harus diperhatikan dalam penggunaan dan pengembangan obat herbal (Wahyuni et al, 2017).…”
Section: Pendahuluanunclassified